John Corey : The Lion - Book 5 - DeMille, Nelson; Brick, Scott (New York : Hachette Audio, 2010)
Libyan terrorist Asad Khalil, known as "The Lion," returns to the U.S. to take care of unfinished business, and the only man who can stop him is John Corey, a special agent for the NYPD's Anti-Terrorist Task Force.
Unabridged.
Compact discs.
Read by Scott Brick.
Keywords: Corey, John (Fictitious character) -- Fiction; Ex-police officers -- Fiction; Terrorism -- Fiction -- Prevention; Audiobooks; New York (N.Y.) -- Fiction; Suspense fiction